Peran dan Tanggung Jawab dalam Pengelolaan Dana dan Transaksi Retail pada Bank Syariah Indonesia (BSI) Area Meulaboh, Aceh Barat - Nur Habillah NST (Indo Publishing, 2026)
Retail fund and transaction management is an important aspect of Islamic banking operations that aims to support the smooth running of business activities and improve the quality of services provided to customers. This article aims to examine the roles and responsibilities in managing retail funds and transactions at Bank Syariah Indonesia Area Meulaboh, Aceh Barat. The method used in this article is a descriptive method by describing various operational activities related to the management of retail funds and transactions. The results of the discussion show that the management of retail funds and transactions includes several activities such as data monitoring, preparing reports on the performance condition of funds and transactions, preparing cooperation documents, filing documents, and carrying out administrative and registration activities such as memos, incoming and outgoing letters, internal notes, and vouchers. In addition, the implementation of duties and responsibilities must comply with internal bank regulations, the prudential principle, sharia compliance, and the principles of Good Corporate Governance (GCG). With proper and well-structured management, banking operational activities can run effectively and efficiently and are able to provide optimal services to the community.